Is Acculturation Related to Obesity in Hispanic/Latino Adults? Results from the Hispanic Community Health Study/Study of Latinos. (29th March 2015) - Isasi, Carmen R.; Ayala, Guadalupe X.; Sotres-Alvarez, Daniela; Madanat, Hala; Penedo, Frank; Loria, Catherine M.; Elder, John P.; Daviglus, Martha L.; Barnhart, Janice; Siega-Riz, Anna Maria; Van Horn, Linda; Schneiderman, Neil
Abstract : Background. The study examined the association of obesity with acculturation in a large and diverse sample of US Hispanic/Latino adults. Methods. The Hispanic Community Health Study (HCHS)/Study of Latinos (SOL) is a community-based cohort study of Hispanic/Latino adults aged 18–74 years (N = 16, 415 ) from four urban areas. Height and weight were directly measured using a standardized protocol. Acculturation was assessed by the Short Acculturation Scale for Hispanics (SASH). Other immigration related variables included place of birth, length of residency in the US, and age at immigration. Odds ratios were calculated to assess the association of overweight, moderate obesity, and extreme obesity (≥ 40 kg/m 2 ) with acculturation and sociodemographic variables. Results. The prevalence of obesity was 42.4% for women and 36.5% for men and varied by field center and Hispanic/Latino background. The strongest predictor of moderate and extreme obesity was length of residency in mainland US. This association was consistent across Hispanic/Latino backgrounds. Acculturation was not significantly associated with obesity. Discussion. The burden of obesity is high among Hispanic/Latino adults. The study findings suggest that prolonged exposure to the environments in these communities, rather than acculturation, is an important risk factor for obesity in this population.